HUBUNGAN KELENTUKAN TOGOK DENGAN AKURASI SMASH BULUTANGKIS PADA SISWA SMA NEGERI 1 CERENTI, KABUPATEN KUANTAN SINGINGI - Rovianda, Okta; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the observation at SMA Negeri 1 Cirenti,Regency Kuantan Singingi if they play badminton, researchers found severalweaknesses related to the ability smash badminton game. The purpose of this study wasto determine how much flexibility regarding the accuracy smash badminton at SMANegeri 1 Cerenti, Regency Kuantan Singingi. This research is an correlation research.is the subject of the study population in general. The population in this study were allmale students of class XI SMA Negeri 1 Cirenti, Regency Kuantan Singingi total of 15persons. based on test results obtained normality test result data are normallydistributed. The calculation result is known to be a great value product momentcorrelation (r count) between flexibility and accuracy smash male student of class XISMA Negeri 1 Cirenti Regency Kuantan Singingi is 0.581. Then I found rhitung =0.581. At degrees of freedom df formula or n-2 (15-2 = 13) significant level of 5% werefound rtabel = 0.514. So rhitung> rtabel or 0.581> 0.514. This shows a correlationbetween the variables X and Y. The result of the calculation is known t = 2.58(attached) while the table t df = n-2 = 15-2 = 13 at 95% confidence interval is 2.16.when t> t table 02:58> 02:16 so that the hypothesis that